Reversible Manifestations of Hypothyroidism causing Diagnostic Dilemma: A Case Series - Kaushik Hazra; Somnath Maitra; Sunetra Roy; Isha Ghosh (Journal of Clinical and Diagnostic Research)
Hypothyroidism causes a wide spectrum of clinical manifestations, with various signs and symptoms. Some symptoms are common and aid in diagnosis, while the uncommon manifestations may be the sole feature causing diagnostic delays, leading to increased morbidity and mortality. Hereby the authors present a combination of three cases (50-year-old female, 22-year-old female, 56-year-old female): ascites, congenital hypothyroidism and myxoedema coma, respectively. Ascites in hypothyroidism responds to treatment and can help avoid unnecessary investigations; however, since this presentation is rare, clinicians should remain alert for low Serum Ascites Albumin Gradient (SAAG) with high protein ascites. myxoedema coma was diagnosed after excluding cerebrovascular accident, sepsis and dyselectrolytemia, with low body temperature serving as a diagnostic clue. Congenital hypothyroidism should be identified and treated promptly to prevent complications in newborns, as thyroid hormone is crucial for growth and development. Deficiency may lead to severe complications in newborns, so it is essential to rule out other causes. The importance of the present case series lies in the fact that hypothyroidism may present with variable manifestations. It is crucial to identify this hormone deficiency, as replacement with widely available thyroid hormone supplementation can promptly reverse some of the clinical manifestations, thereby aiding in accurate diagnosis and timely management with appropriate therapy.